The Influence of Auditor Professional, Idealism Ethical Orientation, and Relativism on Whistleblowing with Legal Protection as a Moderating Variable (Case Study on Aceh Province Government) - Mahlil; Islahuddin; Meutia, Rita (Formosa Journal of Multidisciplinary Research, 2024)
This research examines the influence of auditor professionalism, idealistic ethical orientation, and relativism in whistleblowing, with legal protection as a moderating variable. This research is a population study (census) employing a quantitative and correlational methodology. The population comprises all internal auditors working at the Aceh Province Inspectorate Agency and the Banda Aceh City Inspectorate, totaling 65 individuals. The primary data for this research were collected directly through questionnaires and analyzed using multiple linear regression and moderated regression with an absolute difference value approach. The multiple linear regression analysis findings revealed that auditor professionalism and an idealistic ethical orientation positively influence whistleblowing, whereas relativism negatively impacts whistleblowing. Meanwhile, the research results using moderation regression analysis show that legal protection moderates the influence of auditor professionalism, idealistic ethical orientation, and auditor relativism in whistleblowing.